1977
DOI: 10.1190/1.1440747
|View full text |Cite
|
Sign up to set email alerts
|

Induced Polarization: A Preliminary Study of Its Chemical Basis

Abstract: An investigation of the effect that the in‐situ solution chemistry would have on the induced‐polarization phenomena was carried out by means of laboratory studies of the electrode impedances of metallic and sulfide minerals. Reaction rate theory shows that this effect is largely due to the impedance associated with the diffusion of the ions involved in the charge transfer reaction to and from the reaction sites. This impedance is inversely proportional to the concentration of the reacting ions and inversely pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…We suggest that this decrease could be related to the depletion of electroactive ions (primarily dissolved Fe(II)), the absence of which manifests itself as a lower overall phase response, as suggested by Williams et al [2009]. The importance of electroactive ions in controlling the polarization magnitude at the metallic interface has been extensively discussed in previous studies [Angoran and Madden, 1977;Wong, 1979;Merriam, 2007].…”
Section: Precipitation Of Iron Sulfidesmentioning
confidence: 72%
See 1 more Smart Citation
“…We suggest that this decrease could be related to the depletion of electroactive ions (primarily dissolved Fe(II)), the absence of which manifests itself as a lower overall phase response, as suggested by Williams et al [2009]. The importance of electroactive ions in controlling the polarization magnitude at the metallic interface has been extensively discussed in previous studies [Angoran and Madden, 1977;Wong, 1979;Merriam, 2007].…”
Section: Precipitation Of Iron Sulfidesmentioning
confidence: 72%
“…Further studies have demonstrated a proportional correlation between the size and volumetric enrichment of the metallic minerals and a characteristic frequency response (described by a characteristic relaxation time) [ Pelton et al , 1978; Olhoeft , 1985]. Recent laboratory studies have demonstrated a linear correlation between the imaginary component of the complex conductivity and the total metallic surface area of precipitated metallic minerals [ Slater et al , 2005, 2007], with other studies attributing changes in the frequency‐dependent responses to variations in the concentration of electroactive ions in the pore fluid [ Angoran and Madden 1977; Wong , 1979; Williams et al , 2005] or spatiotemporal changes in location of the mineralization [ Ntarlagiannis et al , 2005a]. Given the multitude of condition‐dependent factors controlling the complex resistivity response, further studies are warranted.…”
Section: Methodsmentioning
confidence: 99%
“…S11; R ct 1 ), facilitating greater rates of electron transfer and a phase response reflective of a diffusion-controlled process (13,14,21). Under such conditions, the composition of the mineral(s) facilitating electron transfer is of minimal importance and in agreement with recently reported results (14) and previous studies investigating the electrochemical nature of the IP response (13).…”
Section: Discussionmentioning
confidence: 99%
“…Among these methods, the induced polarization (IP) technique has shown excellent sensitivity to enhanced microbial activity (5,7,(9)(10)(11)(12). Such studies, combined with theoretical investigations exploring the electrochemical mechanisms underlying the IP response (13,14), suggest it is well suited to monitoring stimulated subsurface bioremediation under field conditions. Analogous to laboratory electrochemical approaches, the IP method involves injection of variable frequency currents into the ground and the measurement of resulting voltage potentials via electrodes located above and below the ground surface.…”
Section: Introductionmentioning
confidence: 99%
“…Even with such simplifications, the Wong model still contains eight parameters with some of them dependent on others. For instance, (1) the diffusion coefficient (D) is considered the same for both the redox-active and redox-passive ions in the electrical double layer (EDL), whilst the passive/active ion concentration ratio is considered very large and the redox-active ions are engaged in diffusive mass transport only; (2) the equilibrium current density (i o ) associated with the transfer of charge (e -) at the metal-electrolyte interface is complicated to define accurately due to the various possible redox reactions, i.e., i o will depend on every specific redox reaction between ions and type of metallic mineral (Angoran and Madden, 1977;Klein and Shuey, 1978). Consequently, i o is directly related to the magnitude of the electrochemical reaction modelling parameters (α, β), and thus to the specific surface conductance of metallic particles, accounting for the interfacial charge storage or capacitive properties; (3) the parameter defining the distance from the metallic mineral surface to the outer Helmholtz plane (l), i.e., the thickness of the Stern layer, directly affects the α parameter and thus the specific surface conductance.…”
Section: Introductionmentioning
confidence: 99%